(untitled) (Chemical Engineering Research Bulletin, 2010)
The efficiency of individual units of an effluent treatment plant (ETP) determines the overall performance of the plant and the final effluent quality. In this study an ETP of a composite textile industry was investigated using this method. Water samples were collected from the main units of the ETP and were analyzed for key parameters. The results were used to diagnose problems with the treatment units and to suggest modifications. From this, a simple but robust methodology was developed for evaluating the performance of the different treatment units and the ETP as a whole that could be implemented by ETP managers on a regular basis to improve the performance so that the effluent leaving the factory meets national standards and conforms to the requirements of international buyers. The results showed that poor management, especially chemical dosing, was seriously affecting the ETP’s performance and that simple measures could address the problems. DOI: 10.3329/cerb.v13i2.3939 Chemical Engineering Research Bulletin 13 (2009) 61-66